2009
DOI: 10.1143/jpsj.78.043704
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization “Steps” on a Kagome Lattice in Volborthite

Abstract: Magnetic properties of the spin-1/2 kagome-like compound volborthite are studied using a high-quality polycrystalline sample. It is evidenced from magnetization and specific heat measurements that the spins on the kagome lattice still fluctuate at low temperature, down to T = 60 mK that corresponds to 1/1500 of the nearest-neighbor antiferromagnetic interaction, exhibiting neither a conventional long-range order nor a spin gap. In contrast, 51 V NMR experiments revealed a sharp peak at 1 K in relaxation rate,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 27 publications
(52 reference statements)
5
111
0
Order By: Relevance
“…In previous studies, polycrystalline samples were obtained by a precipitation, and subsequent heat treatment under hydrothermal conditions 10 . The maximum particle size obtained by this method was on the order of a few micrometers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, polycrystalline samples were obtained by a precipitation, and subsequent heat treatment under hydrothermal conditions 10 . The maximum particle size obtained by this method was on the order of a few micrometers.…”
Section: Methodsmentioning
confidence: 99%
“…The average of (2J 1 + J 2 )/3 was estimated to be 77 K by a high-temperature series expansion fit of the magnetic susceptibility 9 . The nature of the magnetic ground state of volborthite has not been understood in detail yet, but is suggested to be unusual, with strong fluctuations at low temperature (LT) and short-range spin correlations [10][11][12][13][14][15] . One of the reasons for this ambiguity has been the unavailability of single crystals until now.…”
mentioning
confidence: 99%
“…The magnetic susceptibility obeys the Curie-Weiss law ¼ C=ðT þ W Þ above 200 K with W ¼ 115 K, exhibits a broad maximum at 20 K, and approaches a finite value at the lowest temperatures. 11,19) An unusual magnetic transition has been observed near 1 K, [20][21][22][23] which is much lower than W , consistent with strong frustration in a kagome lattice. However, a recent density functional calculation 24) proposed that the frustration is attributed to the competition between a ferromagnetic J and an antiferromagnetic J 00 between second neighbors along the chain (Fig.…”
Section: Introductionmentioning
confidence: 75%
“…The previous theoretical studies indicated that the system is disordered in the ground state. [1][2][3][4][5][6][7][8][9][10][11][12] Experimental studies to observe a novel spin liquid phase have been accelarated since discoveries of several candidate materials; the herbertsmithite, 13,14) the volborthite 15,16) and the vesignieite 17) for the Kagome lattice. However, the spin gap issue is still difficult to solve, because some of numerical methods are not adequate at present.…”
Section: Introductionmentioning
confidence: 99%